Características de historia de vida y patrones de abundancia relativa de Anchoa mitchilli (Teleostei: Engraulidae) en la laguna de Pueblo Viejo, Veracruz - Vélez Jiménez, Susana (Universidad Autónoma Metropolitana, 2008)
Abundance, size structure, reproduction and feeding patterns of Anchoa mitchilli were analyzed in the Pueblo Viejo lagoon, Veracruz, through 12 two-monthly 24-h cycles, in two habitats (with and without submerged vegetation). Abundance did not show differences between habitats, but seasonal significant peaks of abundance occurred during January and March. Moreover, abundance was greater during night hours. The size range of fish varied from 23.36 to 70.46 mm of standard length and a single modal group was found. Mean standard length was greater in the habitat with submerged vegetation. Larger specimens were found in March and smaller ones in May and July; greater sizes were found during the night hours. There was a bimodal pattern in September and May, due to recruitment. Growth per day was calculated by the modal movement, and it was greatest during the first two months of age (0.55 mm/day) decreasing through the first (0.24 mm/day) and the second (0.55 mm/day) semesters., Few organisms live more than one year. Slopes of the weight-length relationship did not show significant differences between males and females. A significant sex ratio with more females was found in March, May, July and 2:00, 10:00, 20:00 hours. Males matured at smaller size than females and testis mean weight was greater than the ovary mean weight. The mean gonosomatic index (GSI) of males and females showed a peak in March defining the reproductive season; moreover the GSI of females was greater during night hours in this month, indicating a nocturnal spawning. Absolute fecundity ranged from 1309 to 4843 ova per female and the mean relative fecundity was of 1454 ova per gram of female weight. There were significant regression relationships between absolute fecundity and female standard length and female weight. An ovotestis case was found. The diet composition was dominated by Copepoda (Acartia tonsa, Euterpina sp.), Tanaidacea (Tanais cavolini, Leptochelia rapax y L. savigny), Amphipoda (Gammarus mucronatus), decapod larvae and fishes (eggs, larvae and rests). So, A. mitchilli the studied system was mainly planktivorous in its feeding habits. Ontogenetic, spatial, seasonal and diel significant differences in the diet were due to individuals size variation, prey size and resources availability.; Se analizaron los patrones de abundancia, estructura de tallas, reproducción y alimentación de Anchoa mitchilli, en la laguna de Pueblo Viejo, Veracruz, a través de 12 ciclos de 24 horas, en dos tipos de hábitat (con y sin vegetación sumergida). Entre hábitats la abundancia no mostró diferencias, pero si entre meses, con pulsos en enero y marzo. Asimismo, la abundancia tendió a ser mayor en la noche que en el día. El intervalo de tallas varió de 23.36-70.46 mm de longitud patrón (LP), encontrándose un solo grupo modal. En el hábitat sin vegetación la LP fue mayor, los individuos más grandes se observaron en marzo y los menores en mayo y julio, siendo las tallas más grandes en la noche. Existieron comportamientos bimodales en septiembre y mayo, debidas a procesos de reclutamiento. Las pendientes de la relación peso-longitud entre machos y hembras no fueron significativamente diferentes. Las proporciones sexuales favorecieron a las hembras en marzo, mayo y julio y a las 2:00, 10:00 y 20:00 horas. Los machos maduraron a una LP menor al de las hembras, siendo el peso de sus gónadas mayor al de las hembras. El índice gonadosomático (IGS) en ambos sexos mostró un pulso máximo en marzo, definiendo este período como la principal temporada reproductiva. Asimismo el IGS de las hembras fue mayor en la noche durante esta temporada, lo que implica desoves nocturnos. Se encontró una fecundidad absoluta de 1309 a 4843 ovocitos por hembra y una fecundidad media relativa de 1454.5 ovocitos/g de peso total, asimismo se encontraron relaciones significativas entre la fecundidad absoluta y la LP y el peso total. Se registró un caso de ovotestis para la especie. Los principales grupos tróficos consumidos por la especie fueron copépodos (Acartia tonsa, Euterpina sp.), tanaidáceos (Tanais cavolini, Leptochelia rapax y L. savigny), anfípodos (Gammarus mucronatus), larvas de decápodos (zoea y megalopa de cangrejos y larvas de peneidos y carideos) y peces (huevos, larvas y restos de aterínopsidos). De este modo A. mitchilli se puede considerar una especie principalmente planctívora, existiendo diferencias significativas en los hábitos de alimento a nivel ontogénico y entre hábitat, épocas y día/noche. Estas diferencias en la dieta se debieron principalmente a cambios en la talla de la especie, al tamaño de las presas y a la disponibilidad de los recursos tróficos.